2011
DOI: 10.3917/eufor.359.0059
|View full text |Cite
|
Sign up to set email alerts
|

Russia's Path to Federalism and Democracy under the Influence of the Council of Europe

Abstract: Résumé Cet article examine le rôle du Conseil de l’Europe dans l’évolution du fédéralisme russe, tant au niveau local que régional. Il tente en particulier de prendre en considération la contribution du Congrès des pouvoirs locaux et régionaux en tant que garant de la Charte européenne de l’autonomie locale. Tout en rendant compte des spécificités du modèle russe de fédéralisme asymétrique, l’article accorde une attention particulière aux défis engendrés par la vague de réformes territoriales initiées par le P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For instance, it is suggested that it enhances the responsibility of regional leaders. However, some researchers have historically expressed concerns that further support to the hierarchical axis of power would hinder the democratic aspirations and offset any opposition (Stahl, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it is suggested that it enhances the responsibility of regional leaders. However, some researchers have historically expressed concerns that further support to the hierarchical axis of power would hinder the democratic aspirations and offset any opposition (Stahl, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Federalism is not only a legal, but also a political and economic matter as well and depends on our history as well as present trends. To analyze the influence of the constitutional amendments upon federalism and the powers of the different regions, the following texts were studied: for common issues on federalism (Benz &Broschek, 2013;Kembayev, 2018;Parker, 2015;Pogegeschi, 2009;Stahl, 2011), for fiscal federalism (Brueckner, 2004;Boadway &Shakh, 2009;Halaskova &Halaskowa, 2015;Komyagin, 2014;Rosefielde &Vennikova, 2004), for the powers of the different regions (Sakwa, 2011).…”
Section: Literature Overviewmentioning
confidence: 99%
“…Moreover, the examination of recent developments in the field democratic transition at local and regional level has shown that Russia, despite first positive signs at the beginning of the reforms in 2000, has still not been able to meet the obligations it committed to when acceding to the CoE. (Stahl 2011) Although this issue mainly concerns Russia, it also has implications for the Barents Region. In 2017, the Norwegian Helsinki Committee, a nongovernmental organisation that works to promote respect for human rights, requested 'Norwegian authorities to increase the emphasis on democracy and human rights in the Russian part of the Barents Region,' because 'on the Russian side, the human rights problems remain very severe' (Human Rights House 2007).…”
Section: Contextualisationmentioning
confidence: 99%
“…If the interests of mayors and their respective regional governors are not aligned, mayors can be replaced (Bigg, ). Moreover, municipalities remain financially dependent on transfers from higher levels of governments (Stahl, ). As a result, it has been argued that local policy is made in discussions between the local and regional authorities (Kourliandskaia et al, ).…”
mentioning
confidence: 99%